The Relationship Between Eating Patterns and Fast Food Consumption on Adolescent Obesity at Bina Utama High School Pontianak - Diska, Fransiska Noviyanti Sekar; Puspita, Widyana Lakshmi; Gambir, Jurianto (MEDICA (International Medical Scientific Journal), 2023)
Obesity or overweight, commonly referred to as excessive weight gain, is a concerning issue among adolescents. Adolescents are the future assets of a nation and are also a vulnerable group at risk of various nutritional problems, including both undernutrition and overnutrition. Obesity is a risk factor for non-communicable diseases such as hypertension, diabetes, and coronary heart disease. The prevalence of overnutrition among adolescents aged 13–15 years in Indonesia is 15.3%, consisting of 8.7% overweight and 6.6% obese. In West Kalimantan, the prevalence is 12.0% for males and 22.0% for females, with an average of 19.3%. This study aims to determine the relationship between eating patterns and fast food consumption with obesity among students at Bina Utama Senior High School in Pontianak. This research used a case-control study design and was conducted at SMA Bina Utama Pontianak on June 22, 2022, using a simple random sampling technique. The total population was 170 students, and the sample size, determined using the Slovin formula, was 62 students. Based on the Chi-square test results, there is a significant relationship between eating patterns and obesity in adolescents, indicated by a p-value of 0.000, and a significant relationship between fast food consumption and obesity, indicated by a p-value of 0.003. Therefore, there is a relationship between eating patterns and obesity, as well as between fast food consumption and obesity among adolescents at SMA Bina Utama Pontianak.